The effect of vibration on flow inside a standing wave thermoacoustic condition - Mohd Sa'at, Fatimah Al-Zahrah; Shikh Anuar, Fadhilah; Zaiham, Nur Afiqah Aina; Yap, Yu Xuan; Saechan, Patcharin (Penerbit UTHM, 2024)
This paper explores the complex relationship between acoustic streaming and vibration in thermoacoustic systems, enhancing the comprehension of these interconnected phenomena in the realm of energy conversion and heat transfer. Thermoacoustic devices are becoming more important for sustainable energy uses. The dynamic interaction between acoustic streaming and vibration is a crucial yet unexplored aspect of the performance of thermoacoustic devices. This research is driven by the necessity of filling current knowledge deficiencies and acknowledging the importance of these factors in the performance of thermoacoustic systems. This study intends to enhance the understanding about acoustic streaming and vibration through the utilisation of numerical simulations and experimental studies. In this paper, a two-dimensional (2D) computational fluid dynamics (CFD) model of standing wave thermoacoustic flow conditions was solved using the SST k-ω turbulence model in ANSYS Fluent to simulate the streaming induced by the vibrational responses within a standing wave thermoacoustic test rig. This numerical prediction is then validated using experimental results from a similar operating condition with a single resonance frequency of 23.6 Hz. Three drive ratios were examined. Disparity between velocity amplitude from CFD simulation and experimental data was observed particularly at the highest drive ratio. As the drive ratio increases, so does the amplitude of the velocity. It was discovered that the model that includes vibration brings the difference in results between the model and the experiment to be smaller and it replicates the closest scenario to the actual condition.